2020
DOI: 10.1186/s40249-020-00736-w
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of intestinal schistosomiasis, alongside increasing urogenital schistosomiasis prevalence, in primary school children on the shoreline of Lake Malawi, Mangochi District, Malawi

Abstract: Background: Intestinal schistosomiasis was not considered endemic in Lake Malawi until November 2017 when populations of Biomphalaria pfeifferi were first reported; in May 2018, emergence of intestinal schistosomiasis was confirmed. This emergence was in spite of ongoing control of urogenital schistosomiasis by preventive chemotherapy. Our current study sought to ascertain whether intestinal schistosomiasis is transitioning from emergence to outbreak, to judge if stepped-up control interventions are needed. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 23 publications
3
39
1
Order By: Relevance
“…This is the first study in Malawi to estimate the prevalence of S. mansoni infection in adults with NCDs. There was high prevalence of S. mansoni infection in this population which is consistent with estimates in school going children in the district of 10 -56.7% (12). This is also consistent reports of an epidemic of both S. mansoni and S. haematobium in the district.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is the first study in Malawi to estimate the prevalence of S. mansoni infection in adults with NCDs. There was high prevalence of S. mansoni infection in this population which is consistent with estimates in school going children in the district of 10 -56.7% (12). This is also consistent reports of an epidemic of both S. mansoni and S. haematobium in the district.…”
Section: Discussionsupporting
confidence: 90%
“…This shift is no less dramatic than along the shores of Lake Malawi where the prevalence has gone from 0% before 2014 to 34.3% (95% CI 27.9 -41.3) among school children in Mangochi in 2017 (6) (11). Follow up studies done after this period establish the emergence of S. mansoni as an epidemic in Mangochi district with prevalence among school children ranging from 10 -56.7% (12).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Cases have continued to increase, especially in schistosomiasis and other NTD endemic areas [385]. This has resulted in the suspension of many MDA programs, leading inevitably to future outbreaks of schistosomiasis [386] and other NTDs [387]. Additionally, it has been suggested that interactions between the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and parasitic infections may result in increased viral susceptibility and more severe outcomes in patients to COVID-19 in NTD-endemic regions [388].…”
Section: Covid-19mentioning
confidence: 99%
“…Malawi is one of the SSA countries where both S. haematobium and Schistosoma mansoni are prevalent and highly focal around most water bodies, especially Lake Malawi (18)(19)(20). In addition, HIV prevalence among adult population (15-49 years) is considered high at 10.6% in SSA region, despite the control efforts including provision of antiretroviral treatment (ART) (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%